Design Optimization of Inverted Switched Reluctance Motor using Ant Colony Optimization Algorithm - Yildiz, Ahmet; Polat, Mehmet; Ozdemir, Mahmut Temel (Ieee, 2018)
Switched Reluctance Motors (SRMs) are widely used as they have extremely simple structure and installation. In SRM, torque, efficiency, amount of torque in unit volume, radial forces depend on motor dimension parameters and it is an important part of motor design. In this study, an ant colony optimization technique was used to determine the optimal motor design parameters of the ISRM. Motor dimension parameters are determined as an optimization problem to maximize average torque and efficiency. In order to calculate the torque and efficiency values, a comprehensive program based on analytical models was developed in Matlab, taking into account the non-linearity of the motor. The optimization process was tested in a 18/12 pole, 3-phase, in ISRM. The determined parameters have reached optimum value, and the torque and efficiency have been maximized. The accuracy of the optimization has been verified with the Maxwell package program.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Switched Reluctance Motor; Ant Colony Optimization Algorithm; Maxwell; Motor Design